Novice Teachers and Mentor Teachers: From a Traditional Model to a Holistic Mentoring Model in the Postmodern Era - Miri Ben-Amram; Nitza Davidovitch (MDPI AG, 2024)
Mentors support novice teachers in the critical stages of their learning, which has an effect on novice teachers' ability to engage in teaching and to stay in the teaching profession for years. The mentor teacher also helps the novice teacher become well integrated and develop professionally. The current study aims to examine the factors that motivate mentor teachers to occupy this position, the guidance and support components of the role and their implementation in the mentoring process, and the frequency and planning of the encounters between mentor and novice teachers, in the context of the Israeli education system. Also examined are the attitudes of mentor teachers towards their role and their perceived ability to operate efficiently. The research population comprises 46 research participants who mentor novice teachers in high schools in Israel. Analysis of their attitudes shows that the factors that motivated them to serve as mentor teachers are related to a consciousness guided by a sense of personal mission and intrinsic motivation to promote novice teachers. Also, factors related to realizing their personal values and aims, such as realizing a vision, personal satisfaction, interest, and challenge, were found to be common. According to self-reported findings, mentor teachers were very helpful to novice teachers on issues such as class management, managing and planning teaching, evaluating students, and nurturing a professional identity. They also supported emotional aspects related to the teaching process, including their sense of efficacy and contact with the students. Mentor teachers felt a great deal of satisfaction with the mentoring process and would recommend this experience to other teachers to a high degree. Hence, a teacher who chooses the profession from a sense of a personal mission in the education system will also see their mentoring role as a mission for the sake of the next generation. Leaders in the education system are advised to develop a more holistic mentoring model that incorporates the traditional mentoring model yet guides us towards a mentoring process that is better adapted to the postmodern era, and is based on a long-term strategy for helping retain novice teachers within the education system.